Teddy bear addition - McGrath, Barbara Barbieri, 1954- (McGrath math., 2014)
"Big bears sort, count, and add tiny teddies in this companion book to the popular McGrath Math series. Catchy speech bubbles accompany lively verse as teddies add single-digit and double-digit numbers from one to fifty